A Childhood Malnutrition Deficiency in India- A Review on Karshya - Nigam, Shruti Keerti; Khare, Abhinav; Patel, Shambhu P; Kumar, Sujit (International Research Journal of Ayurveda & Yoga, 2022)
Ayurveda prioritises prevention over cure. The first of the three pillars, Ahara (Food), is followed by Nidra and Brahmacharya. A balanced diet can help you avoid a lot of common health concerns. Food is significant as a nutritional source, as well as having therapeutic value, and it plays a crucial part in regaining strength lost due to the disease’s detrimental effects throughout the post-treatment phase. Ayurvedic scriptures haphazardly explain nutritional issues. Childhood malnutrition is thought to be the cause of 35% of all fatalities in children under the age of five, as well as 21% of total worldwide disability-adjusted life years lost in children under the age of five. Karshya is a childhood malnutrition-like illness. Similarly, diseases described by diverse Ayurvedic authors as Parigarbhika, Phakka, Balashosha, and Shuska Revati might be linked to undernutrition based on clinical symptoms. These illnesses were linked to one another. The Ayurvedic perspective on dietary disorders such as protein-energy deficiency is highlighted in this article.